Algebra
asked by
Baby_Banana

posted by bobpursley

posted by Ms. Sue

posted by Baby_Banana

posted by Ms. Sue
Respond to this Question
Similar Questions

Algebra
I don't quite understand how to solve matrices with three variables. If I have the equations: 7x4y2z=0 2x3y+z=0.25 2x2y+5z=0 How can I solve this? I saw the explanation in a site but I didn't understand it. They appeared to 
Math, Please Help! I don't understand!
Please help me! I don't understand how to solve. Solve each equation for the given variable. 37. x/a  1 = y/b for x 39. V = 1/3 * pi * r^2 * h for h What do these equations mean? I am super confused. Please help. 
College Algebra
solve systems of equations by graphing... I get how to graph and solve equations but i just don't understand why its coming out wrong u=v 4u=3v3 
math{HELP HELP}
i don't understand these mmath equations. 1) 6y = 24 2)y / 7 = 2 y=_________ On number one i know that if there is a letter next to a number it means multiplication.and i still don't know how to solve it. On number two i don't 
DanHAlgebra 1
Solve the system of equations using the Addition method. 2a + 3b = 1 3a + 5b = 2 Margie: Roger's answer below is correct. If you don't understand it, please try and tell us what you don't understand. He makes it sound so strange 
algebra
how would i find an equation of a line that goes through points(1,6) and (3,10)?? thanks A straight line is y=mx+b Substitute the points to make two equations. 6=m(1)+b 10=m(3)+b Two equations; two unknowns, m and b. Solve for m 
Math
need help with Equations: I don't understand what 4x2x+4=x+10 I don't have a clue how to solve and check it. please help me 
algebra
Solve the system of equations. 9x + y = 2 –4x – y = –17 I don't understand how you solve this. 
TO DRWLS/MATH HELP PLEASE
How do i solve inequalitites with three variables. I still can't figure it outplease help. x+y=1 yz=3 2x+3y+z=1 THE ANSWERS ARE X=3,Y=2,Z=1 i KNOW THE ANSWERS I JUST DON'T KNOW HOW THE BOOK GOT THE ANSWERS . i 'VE TRIED MANY 
Substitution MethodPlz help
Use the Substitution method to solve the system of equations. x + y = 4 x  y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=4 (y+2) + y = 4 solve for y. Then, x= y+2 i don't get